The Roles of PINK1, Parkin and Mitochondrial Fidelity in Parkinson's Disease - Pickrell, Alicia M. (Neuron, 2015)
Understanding the function of genes mutated in hereditary forms of Parkinson's disease yields insight into disease etiology and reveals new pathways in cell biology. Although mutations or variants in many genes increase the susceptibility to Parkinson's disease, only a handful of monogenic causes of Parkinsonism have been identified. Biochemical and genetic studies reveal that the products of two genes that are mutated in autosomal recessive Parkinsonism, PINK1 and Parkin, normally work together in the same pathway to govern mitochondrial quality control, bolstering previous evidence that mitochondrial damage is involved in Parkinson's disease. PINK1 accumulates on the outer membrane of damaged mitochondria, activates Parkin's E3 ubiquitin ligase activity and recruits Parkin to the dysfunctional mitochondrion. Then, Parkin ubiquitinates outer mitochondrial membrane proteins to trigger selective autophagy. This review covers the normal functions that PINK1 and Parkin play within cells, their molecular mechanisms of action, and the pathophysiological consequences of their loss.